Critical whiteness studies and racial justice activism with white student affairs professionals. Issue 180 (1st February 2023) - Ashlee, Kyle C.; Young, Natasha; Wilkinson, Peter
Abstract: Using Critical Whiteness Studies (CWS), two student affairs professionals share their personal narratives about their professional practice. Each reflect on how they challenge white supremacy both personally and professionally. We provide recommendations for using CWS as a framework to inform racial justice activism and support with white student affairs professionals.